Release of Ammonium-N (NH4+) and Nitrate-N (NO3-) by different Leguminous Cover Crops (LCC) planted in peat soils / Muhammad Rahmat Abdul Rahman and Nur Qursyna Boll Kassim - Abdul Rahman, Muhammad Rahmat; Boll Kassim, Nur Qursyna (Faculty of Plantation and Agrotechnology, 2018)
Peat soils is renowned for the low mineral-N concentration, which is crucial for crop's growth. One of the most effective and conserving method of improving the soil mineral-N concentration is by planting leguminous cover crops (LCC) which is common in oil palm plantation area. However, different LCC was found to release different concentration of mineral-N into the soils. Hence, this study aims to determine the concentration of mineral-N in form of ammonium-N (NH4+) and nitrate-N (NO’j b) different types of LCCs namely Mucuna bracteata. Calopogonium mucunoides. Pueraria javanica and Centrosema pubescens as w ell as to evaluate the effects on physico-chemical properties of peat soils. Results showed that Mucuna bracteata released a significant amount of mineral-N into the soils and shows a vigorous growth compared to others. It is suggested that most of the LCCs can survive in acidic peat condition whilst improving the concentration of mineral-N in the soils.